2016
DOI: 10.1093/pcp/pcw101
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression ofOsMYC2Results in the Up-Regulation of Early JA-Rresponsive Genes and Bacterial Blight Resistance in Rice

Abstract: JASMONATE ZIM-domain (JAZ) proteins act as transcriptional repressors of jasmonic acid (JA) responses and play a crucial role in the regulation of host immunity in plants. Here, we report that OsMYC2, a JAZ-interacting transcription factor in rice (Oryza sativa L.), plays an important role in the resistance response against rice bacterial blight, which is one of the most serious diseases in rice, caused by Xanthomonas oryzae pv. oryzae (Xoo). The results showed that OsMYC2 interacted with some OsJAZ proteins i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
81
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 87 publications
6
81
1
Order By: Relevance
“…In rice, OsMYC2 has also been shown to be involved in JA-signalling through interaction with JAZ repressor proteins23. The luciferase activity assay clearly demonstrated that OsMYC2 has a positive impact on the expression of OsNOMT .…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…In rice, OsMYC2 has also been shown to be involved in JA-signalling through interaction with JAZ repressor proteins23. The luciferase activity assay clearly demonstrated that OsMYC2 has a positive impact on the expression of OsNOMT .…”
Section: Resultsmentioning
confidence: 94%
“…As a result, various types of 41 TFs comprising bHLH, MYB, NAC, WRKY, and bZIP families were selected (see Supplementary Table S2), and they included the JA-inductive bHLH factor OsMYC2 and MYB factor OsJAmyb. The expression of OsMYC2 is induced by JA treatment23. Several MYB proteins activate flavonoid biosynthetic genes by interacting with bHLH TFs24.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, treatment with MeJA inhibits root growth in Arabidopsis [34]. Rice plants overexpressing OsMYC2 , a JA response gene, exhibited a dwarf phenotype [35]. Overexpression of allene oxide cyclase in Artemisia annua , had a negative effect on plant growth [36].…”
Section: Discussionmentioning
confidence: 99%